Analisis Dampak Keberadaan PT. Pelindo Multi Terminal Branch Belawan Terhadap Sosial Ekonomi Masyarakat Belawan I Kecamatan Medan Belawan - Vanya Aprilla (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
Ports have assumed a vital part in expanding financial development. As a result, banks, shipping companies, customs, immigration, quarantine, and other activity centers all gather at the port. The purpose of the study is to examine how the existence of Belawan Port affects the well-being of the community around it, as measured by; individuals' pay, work open doors, training, wellbeing, level of safety, and foundation offices. This exploration is subjective examination where the exploration is completed straightforwardly in the field. Huberman which is partitioned into information assortment, information decrease, information show and reaching determinations. Belawan Port ought to have an effect in working on the government assistance of individuals of Belawan I, Medan Belawan Locale, in any case, the state of being found in the truth of life in Medan Belawan Region is that the establishments and spatial preparation of Medan Belawan Locale are still entirely apparent and many ghetto houses are found. organized nearly along the edge of the railroad tracks and in a ghetto region that isn't reasonable for living in. So it tends to be reasoned that the presence of Pt. The people of Belawan I, Medan Belawan District, have not benefited significantly from Pelindo Multi Terminal Branch Belawan.